Influenza vaccines: from whole virus preparations to recombinant protein technology. (January 2014) - Huber, Victor C
Abstract : Vaccination against influenza represents our most effective form of prevention. Historical approaches toward vaccine creation and production have yielded highly effective vaccines that are safe and immunogenic. Despite their effectiveness, these historical approaches do not allow for the incorporation of changes into the vaccine in a timely manner. In 2013, a recombinant protein-based vaccine that induces immunity toward the influenza virus hemagglutinin was approved for use in the USA. This vaccine represents the first approved vaccine formulation that does not require an influenza virus intermediate for production. This review presents a brief history of influenza vaccines, with insight into the potential future application of vaccines generated using recombinant technology.